High-speed compressive wide-field fluorescence microscopy with an alternant deep denoisers-based image reconstruction algorithm. (June 2023) - He, Yilin; Yao, Yunhua; He, Yu; Huang, Zhengqi; Ding, Pengpeng; Qi, Dalong; Wang, Zhiyong; Jia, Tianqing; Sun, Zhenrong; Zhang, Shian
Highlights: Compressive wide-field fluorescence microscopy was developed to break through the speed limit of the camera. An iterative algorithm with alternant deep denoisers was proposed to greatly improve the image reconstruction quality. Compressive wide-field fluorescence microscopy was successfully utilized to observe the high-speed hydrodynamics. Abstract: As an indispensable tool to observe the microcosmic structures and dynamics, wide-field fluorescence microscopy (WFM) has been widely applied in biological and medical areas, but the low imaging speed hinders its applications in high-speed fluorescent dynamics due to the limited frame rate of the camera. Here, we develop a high-speed compressive wide-field fluorescence microscopy (CWFM) to break the imaging speed limitation of conventional WFM. In our CWFM method, a coded aperture temporal compressive imaging technique is introduced into conventional WFM system to accelerate the imaging speed by reconstructing multiple images from every compressed image. An iterative algorithm with alternant deep denoisers of FFDnet and FastDVDnet is designed to reconstruct high-quality sequential images from every compressed image through spatial denoising and temporal constraining. The high-speed imaging ability of CWFM is verified by measuring the movement of fluorescence beads on a slide, and an imaging speed of 2000 Hz is experimentally obtained with an ordinary CMOS camera of 200 Hz, the imaging speed is increased by an order of magnitude. Using our high-speed CWFM system, we successfully observe the hydrodynamics by detecting the flow of fluorescence beads in the water across a corner of microchannel. This technique provides a well-established tool for detecting the high-speed fluid and biological dynamic scene, especially in microflow and cell tracking.